2001
DOI: 10.1074/jbc.m010186200
|View full text |Cite
|
Sign up to set email alerts
|

Glucose 6-Phosphate Hydrolysis Is Activated by Glucagon in a Low Temperature-sensitive Manner

Abstract: Glucagon affects liver glucose metabolism mainly by activating glycogen breakdown and by inhibiting pyruvate kinase, whereas a possible effect on glucose-6-phosphatase has also been suggested. Although such a target is of physiological importance for liver glucose production it was never proven. By using a model of liver cells, perifused with dihydroxyacetone, we show here that the acute stimulation of gluconeogenesis by glucagon (10 ؊7 M) was not related to the significant inhibition of pyruvate kinase but to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…At variance with these results, Ichai et al [61] observed that glucagon increased glucose production from dihydroxyacetone, but decreased the intracellular concentration of Glc-6-P, in perifused hepatocytes. Similarly, infusion of glucagon to anaesthetized rats caused a 1.8-fold increase in hepatic glucose production, but a 2.8-fold decrease in the Glc-6-P level measured after 3 h, again suggesting activation of G6Pase.…”
Section: Short-term Regulationmentioning
confidence: 44%
“…At variance with these results, Ichai et al [61] observed that glucagon increased glucose production from dihydroxyacetone, but decreased the intracellular concentration of Glc-6-P, in perifused hepatocytes. Similarly, infusion of glucagon to anaesthetized rats caused a 1.8-fold increase in hepatic glucose production, but a 2.8-fold decrease in the Glc-6-P level measured after 3 h, again suggesting activation of G6Pase.…”
Section: Short-term Regulationmentioning
confidence: 44%
“…Of note, glucagon concentrations were clamped at constant levels in all experiments in order to assess the effect of insulin in the absence of a concurrent change in glucagon. Since glucagon can increase gluconeogenesis and glucose-6-phosphatase activity (34,35), it is likely that an even greater effect of insulin on EGP may have been observed if glucagon concentrations had been permitted to fall as insulin concentrations increased.…”
mentioning
confidence: 99%
“…However, a recent study on the kinetics of glucose synthesis from dihydroxyacetone and its secretion from rat hepatocytes showed that the accelerating effect of glucagon on glucose release was mostly suppressed at 21°C. This could not be explained by changes in the activity of the involved enzymes (8). It was suggested that, instead, the temperature-sensitive effect of glucagon was on regulating the membrane traffic-based pathway we previously described.…”
Section: Discussionmentioning
confidence: 94%